The Rise of Foreign Investment in China's Banks-Taking Stock - Leigh, Lamin (IMF Working Papers; Working Paper ;, 2006)
The recent wave of foreign investment in China's banks and the prospects of further opening of the banking sector under the WTO agreement suggest that foreign banks are likely to play an increasingly important role in China. This paper takes stock of the involvement of foreign banks in the Chinese banking sector in the perspective of international experience. While in most other countries foreign bank entry took the form of direct takeover or majority shareholding, foreign investments in China's banks have been minority shareholdings with very limited management involvement. The paper concludes that China appears to be well positioned to benefit from further opening of the banking sector to foreign investors. International experience suggests that greater competition from and participation of foreign banks can in general bring important benefits if appropriate incentives and sufficient opportunities are created.